Latin Epigraphy, an interdisciplinary approach to the ancient world - Funari, Pedro Paulo A.; Garraffoni, Renata S. (Classica - Revista Brasileira de Estudos Clássicos, 2005)
Conference Report. Instrumenta Inscripta Latina, Austria, May 5th to 8th, 2005.